Drama and expansion in Arabic literature - Sirajuddin, D Mohammed (IIUC Studies, 2009)
The full text of this article is in Arabic - see PDF below. doi: 10.3329/iiucs.v3i0.2672 IIUC STUDIES Vol. - 3, December 2006 (p 23-34)